2023
DOI: 10.1371/journal.pone.0288260
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in silico studies for the identification of anti-cancer and antibacterial peptides from camel milk protein hydrolysates

Abstract: Today, breast cancer and infectious diseases are very worrying that led to a widespread effort by researchers to discover natural remedies with no side effects to fight them. In the present study, we isolated camel milk protein fractions, casein and whey proteins, and hydrolyzed them using pepsin, trypsin, and both enzymes. Screening of peptides with anti-breast cancer and antibacterial activity against pathogens was performed. Peptides derived from whey protein fraction with the use of both enzymes showed ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…The decomposers produced from pepsin possess antibacterial activity, and when monitoring the antibacterial ability of these decomposers, a decrease in the growth of Escherichia coli and Staphylococcus aureus bacteria, respectively, was observed (46). These results are also consistent with the findings of Theolier (29,43).. Effect of elastin hydrolysates added to ground beef stored in cold storage on bacteria: Chart (1) shows the effect of elastin hydrolysates added to fresh, chilled minced beef on Total psychrophilic count, E.coli bacteria, and Total Plate Count, as it was observed that there was a significant increase (P<0.01) in the number of bacteria for T 1 6.67, 3.05, and 8.15 CFU/gm meat in TBC4, E.coli, and TBC37, respectively, while elastin hydrolysates reduced the number of bacteria, especially with the T 2 and T 3 treatments, as the number of bacteria in T 2 reached 4.86, 2.34, and 5.58, and T 3 reached 5.21, 2.55, and 5.83 CFU/gm. meat for TPC4, E.coli, and TPC37 bacteria, respectively.…”
Section: Ecolisupporting
confidence: 93%
See 1 more Smart Citation
“…The decomposers produced from pepsin possess antibacterial activity, and when monitoring the antibacterial ability of these decomposers, a decrease in the growth of Escherichia coli and Staphylococcus aureus bacteria, respectively, was observed (46). These results are also consistent with the findings of Theolier (29,43).. Effect of elastin hydrolysates added to ground beef stored in cold storage on bacteria: Chart (1) shows the effect of elastin hydrolysates added to fresh, chilled minced beef on Total psychrophilic count, E.coli bacteria, and Total Plate Count, as it was observed that there was a significant increase (P<0.01) in the number of bacteria for T 1 6.67, 3.05, and 8.15 CFU/gm meat in TBC4, E.coli, and TBC37, respectively, while elastin hydrolysates reduced the number of bacteria, especially with the T 2 and T 3 treatments, as the number of bacteria in T 2 reached 4.86, 2.34, and 5.58, and T 3 reached 5.21, 2.55, and 5.83 CFU/gm. meat for TPC4, E.coli, and TPC37 bacteria, respectively.…”
Section: Ecolisupporting
confidence: 93%
“…Who indicated that the use of essential oils and niacin in meat sausages reduces the microbial load. It agrees with Uma and Ravi (43). who studied the effectiveness of some carotenoids extracted from shrimp shells, which showed antibacterial activity, especially Bacillus sp, Achromobacter sp.…”
Section: Ecolisupporting
confidence: 90%
“…Furthermore, hydrolysate camel casein digested by trypsin showed antibacterial activity against S. aureus and E. coli , with inhibition zone 3.11 and 1.07 mm, respectively. The total mass of hydrolysate camel casein used in the previous study was 60 μg [20] …”
Section: Resultsmentioning
confidence: 99%
“…Peptides released from casein treated with trypsin proved to be the most effective against Klebsiella pneumoniae, and in the case of Pseudomonas aeruginosa, treated with pepsin and trypsin in turn. Whey protein hydrolysates formed by pepsin exhibited their strongest antibacterial activity against Staphylococcus aureus and Escherichia coli, of which in the case of the last group of bacteria, an identical effect was obtained using trypsin separately [197].…”
Section: The Role Of Milk Bioactive Peptides On the Organismsmentioning
confidence: 90%
“…The presence of milk protein peptides in the intestinal lumen can have a stimulating effect on mucus production or mineral absorption or promote the inhibition of inflammation [77]. Peptides formed via enzymatic digestion exhibit health-promoting properties, among which we can also include antihypertensive, anticancer, antioxidant, antidiabetic, antimicrobial, and many other properties [195][196][197]. For this reason, bioactive milk peptides have found their use as dietary supplements, functional food ingredients, or pharmaceuticals to improve health and thereby reduce the incidence of chronic diseases [82].…”
Section: The Role Of Milk Bioactive Peptides On the Organismsmentioning
confidence: 99%